ANALISIS CITRA PEREMPUAN DAN IDEOLOGI PATRIARKI DALAM NOVEL PEREMPUAN BERKALUNG SORBAN - Nurianti Siagian; Monalisa Frince Sianturi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The novel Perempuan Berkalung Sorban by Abidah El Khalieqy presents a complex portrayal of women’s lives in an Islamic boarding school environment that is strongly influenced by patriarchal ideology. This article aims to analyze the image of women and the forms of patriarchal ideology represented through the female characters in the novel, particularly the character Annisa. This study employs a descriptive qualitative method using a feminist literary criticism approach. The data were obtained through an intensive reading of the novel and collected in the form of relevant quotations, which were then classified according to the focus of the analysis. The findings show that the image of women in the novel is depicted as oppressed, obedient, and restricted in their freedom; however, at the same time, women are also portrayed as developing into critical, progressive individuals who dare to resist injustice. Patriarchal ideology is represented through power relations within the family, forced marriage practices, restrictions on women’s education, verbal and physical violence, as well as the use of gender-biased religious interpretations. The novel not only reflects the reality of gender inequality but also serves as a medium of social criticism against patriarchal structures and highlights women’s struggles to gain freedom and equality. ABSTRAK Novel Perempuan Berkalung Sorban karya Abidah El Khalieqy menghadirkan gambaran kompleks mengenai kehidupan perempuan dalam lingkungan pesantren yang masih kuat dipengaruhi oleh ideologi patriarki. Artikel ini bertujuan untuk menganalisis citra perempuan serta bentuk-bentuk ideologi patriarki yang direpresentasikan melalui tokoh-tokoh perempuan dalam novel tersebut, khususnya tokoh Annisa. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan kritik sastra feminis. Data diperoleh melalui pembacaan intensif terhadap teks novel, kemudian dikumpulkan dalam bentuk kutipan-kutipan yang relevan dan diklasifikasikan sesuai fokus kajian. Hasil analisis menunjukkan bahwa citra perempuan dalam novel digambarkan sebagai sosok yang tertindas, patuh, dan dibatasi ruang geraknya, namun pada saat yang sama juga berkembang menjadi pribadi yang kritis, progresif, serta berani melakukan perlawanan terhadap ketidakadilan. Ideologi patriarki ditampilkan melalui relasi kuasa dalam keluarga, praktik perkawinan paksa, pembatasan pendidikan perempuan, kekerasan verbal maupun fisik, serta penggunaan tafsir agama yang bias gender. Novel ini tidak hanya menggambarkan realitas ketimpangan gender, tetapi juga menjadi media kritik sosial terhadap struktur patriarki dan bentuk perjuangan perempuan dalam memperoleh kebebasan serta kesetaraan.